POST-EVAPORITIC RESTRICTED DEPOSITION IN THE MIDDLE MIOCENE CHOKRAKIAN-KARAGANIAN OF EAST CRIMEA (UKRAINE) - Peryt T.M.; Jasionowski M.; Peryt D.; Poberezhskyy A.V.; Durakiewicz T. (My University, 2004)
In the Middle Miocene of East Crimea, gypsum evaporites formed in a shallow basin from mixed seawater–nonmarine waters are overlain by marl, siltstone and claystone which contain a few horizons of stromatolitic limestone. The thickness and abundance of the stromatolitic horizons increase up the section. In the siliciclastic portion of the section, a very poor and taxonomically impoverished assemblage of benthic foraminifers (Jadammina, Nonion, Haynesina, Astrononion and Eponides) is recorded. It is typical for a shallow water marsh or lagoon environment with a lowered salinity. Accordingly, the brackish conditions prevailing during gypsum precipitation in East Crimea continued afterwards, although at the end of evaporite deposition the basin became desiccated and then it was rapidly reflooded by brackish water.
Keywords: Stromatolites; Middle Miocene; Palaeoenvironments; Foraminifers; Geochemistry; Evaporite basins; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен